Optimization of response surface methodology by D-optimal design for alkaline hydrolysis of crude palm kernel oil - Murad Bahadi; Mohamad Firdaus Yusoff; Jumat Salimon; Darﬁzzi Derawi (Penerbit Universiti Kebangsaan Malaysia, 2020)
Crude palm kernel oil (CPKO) was converted into its free fatty acids (FFAs) via alkaline hydrolysis. The reaction optimization was performed using Response Surface Methodology (RSM) through D-optimal design to optimize the conducted hydrolysis parameters. The optimization parameters were varied from 1.5 to 2.5 h of reaction time, 50-70°C of reaction temperature, and ethanolic KOH concentration 1-2 M. The highest percentage of free fatty acids was 98 ± 0.7 % with a percentage fatty acid yield of 84.7 ± 0.6 % under optimal conditions, which were 2.16 h of reaction time, 1.77 M ethanolic KOH concentration, and 70°C reaction temperature. High-temperature Capillary Column Gas Chromatography (GC-FID) and Nuclear Magnetic Resonance-Fourier Transform Infrared Spectroscopy (NMR-FTIR) were employed to characterize the product. The physicochemical properties of fatty acids were also tested. The acid value, iodine value, and hydroxyl value of the fatty acids obtained were 275.4 ± 0.7 mg NaOH/g, 21.8 ± 0.2 g I2 / 100 g, and 168.2 ± 0.1 mg KOH/g, respectively.